Optimizing Prison Authority in Death Row Inmate Rehabilitation - Rizki Ananda, Azzahra (Yayasan pendidikan dzurriyatul Quran, 2025)
Indonesia’s correctional system has gradually shifted from a retributive model toward a rehabilitative approach grounded in Pancasila and human rights principles. Yet, death row inmates occupy a unique and vulnerable position due to the absence of explicit regulatory frameworks governing their rehabilitation. This study aims to explore the urgency, implementation, and ideal model for the rehabilitation of death row inmates in Indonesian correctional institutions. Employing an integrated normative and empirical juridical method, the research analyzes statutory regulations, field observations, and interviews with relevant stakeholders. The findings reveal that various spiritual, psychological, vocational, and educational programs have been initiated, though these practices lack national standardization. Legal uncertainty and prolonged execution delays significantly affect inmates’ psychological well-being and expose correctional staff to institutional risk. The study recommends a human rights-based rehabilitative model supported by specific regulations, staff training, and consistent external oversight. Comprehensive correctional reform is essential to ensure justice, security, and humanity in the treatment of all inmates, particularly those facing capital punishment